Experimental approaches to conservation biology - Gordon, Malcolm S.; Bartol, Soraya M., 1970- (University of California Press, 2004)
Evidence is increasingly indicating that the current rate of species extinction is reaching its highest level since the asteroid collision 65 million years ago, & that humans are laregly responsible. This volume explores aspects of a looming crisis.